Study on interval rupture mechanism and support optimization of layered roof. (November 2022) - Zhao, Bingchao; Wang, Jingbin
Highlights: Considering the influence of the failure of the two sides of the roadway on the roof deformation, the mechanical model of the fixed beam and the mechanical model of the simple beam of the single-layer rock beam under the combined action of the vertical stratum load and the horizontal load are established by using the theory of material mechanics and structural mechanics. The analytical solution of the internal force at the end and midspan of the rock beam and the extreme stress at the upper and lower edges of the midspan of the rock beam are derived. Based on the equivalent calculation model of physical and mechanical parameters of layered roof, the failure criterion of layered roof is analyzed. According to the static equilibrium equation of the rock beam in the horizontal direction, the calculation formulas for determining the position of the stress neutral layer of the rock beam under the condition of fixed support and simple support are derived, and the main influencing factors of the height of the tensile zone of the rock beam are discussed. In this paper, the rock layer below the neutral layer is considered as the potential caving rock mass, and it is proposed that the mid-span position of the neutral layer of each rock layer is considered as the vertex of each invisible caving arch. Based on the theory of partition fracture, it is proposed that the layered roof is the interval fracture based on the neutral layer theory (potential caving rock mass), and the targeted grouting filling is proposed for the failure of each layer of the layered roof. The overall strength of layered roof is improved. Abstract: In view of the practical engineering problem that the layered roof of deep roadway is easy to deform and destroy but difficult to support, the mechanical model of deformation and failure of roof rock beam under the combined action of vertical stratum load and horizontal load is established by using the theory of material mechanics and structural mechanics. The analytical solution of internal force at the end and midspan of rock beam and the extreme stress at the upper and lower edges of rock beam midspan are discussed. Based on the equivalent calculation model of physical and mechanical parameters of layered roof, the failure criterion of layered roof is proposed. According to the static equilibrium equation of the rock beam in the horizontal direction, the position of the stress neutral layer and the height of the tensile region of the rock beam under the conditions of fixed support and simple support are analyzed. The results show that the tensile zone height of rock beam is positively correlated with vertical stratum load and horizontal lateral pressure, and negatively correlated with elastic modulus and thickness-span ratio of rock beam. Under the same span condition, when the fixed rock beam is transformed into a simply supported rock beam, the stress neutral layer will move down and the height of the tensile region will decrease. However, after the instability of the rock mass in the roadway sidewall leads to the increase of the effective span, the stress neutral layer of the roof rock beam will move up and the height of the tensile region will increase. Based on the neutral layer distribution characteristics of layered roof and self-stable invisible arch theory, the invisible equilibrium arch distribution law of each rock beam in layered roof is analyzed. Finally, the rationality of the above view is verified by an example of a working face.